2021
DOI: 10.1002/mds.28774
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Prion Protein Mediates α‐Synuclein Uptake, Localization, and Toxicity In Vitro and In Vivo

Abstract: A BS TRACT: Background: The cellular prion protein (PrP C ) is a membrane-bound, multifunctional protein mainly expressed in neuronal tissues. Recent studies indicate that the native trafficking of PrP C can be misused to internalize misfolded amyloid beta and α-synuclein (aSyn) oligomers. Objectives: We define PrP C 's role in internalizing misfolded aSyn in α-synucleinopathies and identify further involved proteins. Methods: We performed comprehensive behavioral studies on four transgenic mouse models (ThySy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
(135 reference statements)
3
13
0
Order By: Relevance
“…Although the molecular mechanisms responsible for spreading pathologic αSyn are poorly understood, a growing body of evidence indicates that de novo misfolding and/or neuronal internalization of aggregated αSyn facilitates conformational templating of endogenous αSyn monomers in a prion-like manner [77]. Recent studies demonstrating that cellular prion protein (PrP C ) mediates αSyn uptake, localization, and toxicity in vitro and in vivo confirmed previous results which showed that PrP C internalizes soluble misfolded αSyn, indicating its important role in its internalization required for the intercellular spread of αSyn [78]. Cell intrinsic features also may play a critical role in the formation of pathologic αSyn, such as mechanisms that increase endogenous αSyn levels, selective expression profiles in distinct neuron types, altered function of proteins involved in αSyn synthesis and degradation, and oxidative stress.…”
Section: Self-propagation Of Prionoidsmentioning
confidence: 56%
“…Although the molecular mechanisms responsible for spreading pathologic αSyn are poorly understood, a growing body of evidence indicates that de novo misfolding and/or neuronal internalization of aggregated αSyn facilitates conformational templating of endogenous αSyn monomers in a prion-like manner [77]. Recent studies demonstrating that cellular prion protein (PrP C ) mediates αSyn uptake, localization, and toxicity in vitro and in vivo confirmed previous results which showed that PrP C internalizes soluble misfolded αSyn, indicating its important role in its internalization required for the intercellular spread of αSyn [78]. Cell intrinsic features also may play a critical role in the formation of pathologic αSyn, such as mechanisms that increase endogenous αSyn levels, selective expression profiles in distinct neuron types, altered function of proteins involved in αSyn synthesis and degradation, and oxidative stress.…”
Section: Self-propagation Of Prionoidsmentioning
confidence: 56%
“…The S2R is a therapeutic target under investigation for α-synucleinopathies and CT1812 is currently in Phase 2 trials, being developed by Cognition Therapeutics, for dementia with Lewy bodies (NCT05225415). Support for targeting the S2R derives from α-synuclein binding to PrP c [ 42 ], and the finding that S2R modulators block α-synuclein oligomer toxicity in neurons [ 4 ]; this is a topic discussed in greater detail below.…”
Section: α-Synucleinopathies—parkinson’s Disease and Dementia With Le...mentioning
confidence: 99%
“…S2R in close association with PGRMC1 regulates cell pathways known to be impaired in α-synucleinopathies, such as autophagy, vesicle trafficking, and lipid synthesis. Similar to amyloid-β oligomers, α-synuclein oligomers interact with PrP c [ 42 ]. α-Synuclein interacts with PrP c to induce cognitive impairment through metabotropic glutamate receptors, and blockage of these glutamate receptor-mediated signaling events restores cognitive deficits [ 42 ].…”
Section: S2r Modulators As a Promising Therapeutic Approach For Age-r...mentioning
confidence: 99%
“…Besides minimal methodological differences in recombinant α-syn purification and oligomer preparation, no obvious evidence justifies these contradictory results. A role of prion protein in α-synOs intercellular transport and pathological transmission has been recently hypothesized ( Urrea et al, 2018 ; Rösener et al, 2020 ) but the link with the direct binding of α-synOs to PrP c still needs further investigation ( Legname and Scialò, 2020 ; Thom et al, 2021 ).…”
Section: Oligomers and Prion Proteinmentioning
confidence: 99%